Dynamics of stochastic partly dissipative systems on time-varying domain. Issue 1 (2nd January 2017) - Zhang, Zhen; Huang, Jianhua
ABSTRACT: This article is devoted to stochastic partly dissipative systems (SPDS) defined on time-varying domain expending in time. The definition of a space–time trace class Wiener process on time-varying domain is presented by combining a time trace class Wiener process with a spatial intensity defined on time-varying domain. Some nice properties for Wiener process on time-varying domain are also presented. We develop a new penalty method to establish the existence and uniqueness of variational solution of SPDS with additive noise on time-varying domain. The existence of global attractor for the process generated by variational solution is also obtained.